Workshop report: East Africa Strategic Futures, Food Security, the Environment and Livelihoods - CGIAR Research Program on Climate Change, Agriculture and Food Security (2012)
The CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) in partnership with Regional Office of the Society for International Development in Eastern Africa (SID-EA) hosted a Strategic Futures Workshop to use and discuss the regional scenarios that examine key future socio-economic issues for East African food security, environments and livelihoods. Scenarios are strategic tools that allow leaders to take into consideration various plausible futures in development planning. This policy workshop brought together climate change, agricultural and food security researchers and policymakers in conducting a visioning exercise aimed at developing policy and investment options, on climate smart agricultural research and development priorities within the East Africa region. Through challenging techniques such as visioning and back-casting, the participants of the workshop ultimately developed strategies and policies for East Africa, The workshop also enabled the development of potential partnerships on the subjects of focus. This report documents the process and the outcomes of the activities during the workshop.